Computational methods in water resources : proceedings of the XVth International Conference on Computational Methods in Water Resources (CMWR XV), June 13-17, 2004, Chapel Hill, NC, USA. - Miller, Cass T. (Cass Timothy) (Developments in water science, 2004)
The XV International Conference on Computational Methods in Water Resources (CMWR XV) was held in Chapel Hill, North Carolina, 13-17 June 2004. The conference was sponsored by the Department of Environmental Sciences and Engineering, School of Public Health, The University of North Carolina at Chapel Hill. This two-volume set represents the reviewed and edited proceedings of this meeting, including 156 papers. In addition, many posters were presented at the meeting, which are not included in this formal written record. These collective works include contributions by many of the leading water resources research groups from around the world. Broad in scope, these papers address numerous aspects of water resources systems, ranging from the microscale to the field scale and from the very fundamental to the most compelling and important of applications. Virtually all major classes of numerical methods for water resources problems are represented in these proceedings, from the evolution of traditional approaches to the latest in methods of recent invention. As has been traditional at past CMWR meetings, subsurface hydrology, land surface hydrology, and surface water hydrology are well represented.